The sport burnout syndrome in Brazil - Daniel Alvarez Pires; Marisa Lúcia de Mello Santiago; Dietmar Martin Samulski; Varley Teoldo da Costa (Journal of Physical Education (Maringá), 2012)
Burnout syndrome, considered a reaction to chronic stress, has as its main characteristics emotional exhaustion, a reduced sense of achievement, and depersonalization. The aim of this research consisted in revising the studies concerning this syndrome in the Brazilian sports environment. The method used to select the published work consisted of researching computer data bases of journals from the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), and searching the citations found in these data bases published until may 2011. No empirical studies were found with respect to Burnout in referees and fitness coaches. Eight researches were found and classified into three topics for discussion: (a) implications of Burnout on sport training; (b) psychometric instrument for measuring (c) manifestation of Burnout in athletes and coaches. It was concluded that there is a lack of researches about Burnout in the Brazilian sport environment.